2022
DOI: 10.1021/acs.jafc.2c03009
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid, an Active Ingredient in Coffee, Combines with DOX for Multitarget Combination Therapy of Lung Cancer

Abstract: Adjuvant diet therapy is an important means of comprehensive treatment of cancer. It is recognized by patients for its high safety, painlessness, and ease to operate. However, the development of adjuvant dietary therapy is limited by unclear targets and unclear anticancer mechanisms. In this work, caffeic acid was found as an inhibitor of TMEM16A with an IC 50 of 29.47 ± 3.19 μM by fluorescence quenching and whole-cell patch-clamp experiments. Caffeic acid regulated the proliferation, migration, and apoptosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 46 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…It can be derived from almost all plants, especially coffee, thyme, and olive plants. The properties such as antitumor, antioxidative, and anti-inflammatory make this compound a potential option for diseases which are induced by any kind of exogenous and endogenous stress [ 339 ]. The antioxidant role protects cells from oxidative damage caused by reactive oxygen species (ROS).…”
Section: Herbal Drugs In Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It can be derived from almost all plants, especially coffee, thyme, and olive plants. The properties such as antitumor, antioxidative, and anti-inflammatory make this compound a potential option for diseases which are induced by any kind of exogenous and endogenous stress [ 339 ]. The antioxidant role protects cells from oxidative damage caused by reactive oxygen species (ROS).…”
Section: Herbal Drugs In Skin Cancermentioning
confidence: 99%
“…The findings demonstrated that the inhibitory effects were better with the less dose of two drugs as compared to double dose of single drug. In this study, CA was augmenting the effects of DOX by inhibiting proliferation, migration, and inducing apoptosis [ 339 ]. Such various evidence validates the application of CA in downregulating molecular pathways which are responsible for the initiation of inflammatory conditions which leads to the development of precancerous lesions.…”
Section: Herbal Drugs In Skin Cancermentioning
confidence: 99%
“…30 It has been found that ingredients in various functional foods showed anticancer activity, such as broccoli, 31 ginger, 32 and coffee. 33 The main elements limiting their application include the high effective concentration of these ingredients and the low content in food so making it difficult to produce an anticancer effect by only dietary sources. 34 In addition, the extraction processes of some components are complex and have low druggability, so they cannot be produced on a large scale.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Food adjuvant therapy is becoming popular in cancer treatment because it enhances treatment effects and reduces side effects . It has been found that ingredients in various functional foods showed anticancer activity, such as broccoli, ginger, and coffee . The main elements limiting their application include the high effective concentration of these ingredients and the low content in food so making it difficult to produce an anticancer effect by only dietary sources .…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid, a metabolite derived from chlorogenic acid, is also described in the literature as a phenolic compound found in coffee's silver skin (Figure 5). Despite possessing a lower commercial value compared to CQAs (1 g of caffeic acid equivalent to $50), it boasts a wide range of biological activities, including antioxidant, antiviral, anticancer, antiplasmodial, and antidiabetic properties [93][94][95].…”
Section: Coffee (Coffea Spp)mentioning
confidence: 99%